Implementing the ADDIE Model in Developing Learning Videos Skills of Integrated Health Post Cadres - Ketut Suarayasa; Miranti Miranti; Elliyane Bangkele; Diah Mutiarasari (Newinera Publisher, 2025)
Integrated Health Service Posts (Posyandu) in the era of primary care transformation provide services for all life cycle targets. They require Posyandu cadres who know and understand the 25 basic skills. The purpose of this study was to describe the development of video-based learning media on Posyandu cadre skills to improve their knowledge and skills in Palu City. The research used research and development (R&D). The study was conducted at the Mamboro Community Health Center in Palu City. The video creation process used the ADDIE (Analyze, Design, Development, Implementation, Evaluation) model, which divides the planning process into several steps and organizes each step into a logical sequence. The output from the previous step is then used as input for the next step. The research results indicate that the development of a video for teaching skills for Posyandu (Integrated Health Post) cadres can be successfully implemented through the stages of analysis, design, development, implementation, and evaluation. The validator team gave a feasibility score of 96% (Very feasible) for the media and 94.6% (Very feasible) for the material respectively. The trial results demonstrated positive perceptions from the health workers and Posyandu cadres who participated in the video trial. They noted that the video presented a realistic simulation of Posyandu activities in visual and audio form that was easy to follow. The ADDIE model is suitable for developing learning videos because each stage requires specific study and treatment, ensuring accountability for the resulting product.